2016
DOI: 10.1242/dmm.024786
|View full text |Cite
|
Sign up to set email alerts
|

A high-fat jelly diet restores bioenergetic balance and extends lifespan in the presence of motor dysfunction and lumbar spinal cord motor neuron loss in TDP-43A315T mutant C57BL6/J mice

Abstract: Transgenic transactivation response DNA-binding protein 43 (TDP-43) mice expressing the A315T mutation under control of the murine prion promoter progressively develop motor function deficits and are considered a new model for the study of amyotrophic lateral sclerosis (ALS); however, premature sudden death resulting from intestinal obstruction halts disease phenotype progression in 100% of C57BL6/J congenic TDP-43A315T mice. Similar to our recent results in SOD1G93A mice, TDP-43A315T mice fed a standard pelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…Additionally, motor behavior was scored as previously described (34, 39) and Nlk reduction ameliorated gait impairment, tremor, hindlimb clasping, and kyphosis between P14-P22 (Figure 5J-N, Supplemental Figure 8, and Supplemental Video 1). Finally, because altering diet may affect the course of disease in transgenic ALS mouse models (40), we raised an independent cohort of Thy1-TDP Tg/Tg animals on a high fat/gel food diet and observed a similar improvement in motor behavior with a greater extension of survival with P1 Nlk ASO injections (Supplemental Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, motor behavior was scored as previously described (34, 39) and Nlk reduction ameliorated gait impairment, tremor, hindlimb clasping, and kyphosis between P14-P22 (Figure 5J-N, Supplemental Figure 8, and Supplemental Video 1). Finally, because altering diet may affect the course of disease in transgenic ALS mouse models (40), we raised an independent cohort of Thy1-TDP Tg/Tg animals on a high fat/gel food diet and observed a similar improvement in motor behavior with a greater extension of survival with P1 Nlk ASO injections (Supplemental Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…This phenotypic artifact masked neurodegeneration in these mice, however a posterior study showed that when feeding the animals a high fat gel based diet extended their lifespan showing progressive ALS phenotype. 123 Subsequent mouse models were developed with more restricted promoters to isolate TDP-43 effects in the brain; however the results have also been highly heterogeneous. 36,122,124 Very recently a new TDP- 43 Altogether, further research is still needed to generate improved animal models in order to understand TDP-43 implication in disease and be used as tools to discover new drugs.…”
Section: Cellular and Animal Models To Evaluate Tdp-43 Homeostasismentioning
confidence: 99%
“…To date, no efficient treatment for ALS is available and studies leading to potential new treatment strategies remain of great importance [199,200]. Efforts have been made to find new therapeutics based on the suggested metabolic defects [8,98,[201][202][203][204][205], but partly due to the lack of knowledge about the metabolic defects in ALS, this search has not yet been successful. Therefore, we believe that the tools discussed in this review could play an important role in the search for new treatment strategies in ALS.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%